The Effect of Skim Milk and Carboxy Methyl Cellulose Concentrations on the Characteristics of Tamarillo Velva (Cyphomandra betacea) - Salvania, Hafidha; Ratna Yulistiani; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This research aims to determine the effect of skim milk and Carboxy Methyl Cellulose (CMC) concentrations and determine the best formulation for making tamarillo Velva. The research used a Completely Randomized Design (CRD) with 2 factors and 2 replications. Data analysis using ANOVA was continued with the Duncan multiple range test (DMRT) at a confidence level of 5%. The 1st factor is the concentration of skim milk (5% (S1), 7.5% (S2), 10% (S3)). The 2nd factor is the CMC concentration (0.25% (C1), 0.50% (C2), and 0.75% (C3)). The parameters observed include analysis of total dissolved solids, vitamin C content, protein content, antioxidant analysis, overrun, melting time, viscosity, and organoleptic analysis, including texture, taste, aroma, and color. The results of the treatment with the concentration of skim milk and CMC had a significant effect on viscosity, overrun, melting time, vitamin C content, total dissolved solids, texture, and color. The best treatment in this study was velva with a concentration of skim milk (10%) and CMC (0.25%) with an antioxidant activity value of 28.20%, vitamin C 16.56 mg/100g, protein 1.60 g, total dietary fiber 14.05%, total dissolved solids 26.9°brix, overrun 15.78%, viscosity 2079 m.Pas, melting time 20.83 minutes, texture scoring test 3.32 (quite soft), and average preference for taste 3.64 (somewhat like), color 3 (somewhat like), aroma 3.6 (somewhat like).